2002
DOI: 10.1046/j.1365-2168.2002.02262.x
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of compliance with the UICC/AJCC staging system in the staging of gastric cancer

Abstract: These results reflect the need for improved N staging across the region to aid the appropriate multimodal treatment of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 14 publications
3
35
1
Order By: Relevance
“…This means that pre-operative staging should be as rigorous as possible in order to thoroughly define patients with diffuse or unresectable disease. Our rate of operability is still high (86%), similar to other important series published until the 90's (2) , though it has decreased since the second half of the second period when laparoscopy assessment was added as part of the staging, thereby coming closer to more recent series (39,53) . This is because laparoscopy can assess peritoneal implants that are difficult to detect in routine imaging exams and, in such cases, precludes palliative surgery (24,35) , leading to complementary procedures, such as neo-adjuvant chemotherapy (9,32,33,43,46) .…”
Section: Discussionsupporting
confidence: 69%
“…This means that pre-operative staging should be as rigorous as possible in order to thoroughly define patients with diffuse or unresectable disease. Our rate of operability is still high (86%), similar to other important series published until the 90's (2) , though it has decreased since the second half of the second period when laparoscopy assessment was added as part of the staging, thereby coming closer to more recent series (39,53) . This is because laparoscopy can assess peritoneal implants that are difficult to detect in routine imaging exams and, in such cases, precludes palliative surgery (24,35) , leading to complementary procedures, such as neo-adjuvant chemotherapy (9,32,33,43,46) .…”
Section: Discussionsupporting
confidence: 69%
“…10 Therefore, we sought to identify the proteins that may be involved in invasion and lymph node metastasis of gastric cancer by comparing The overall survival rate of all gastric cancer cases (n ϭ 93) was correlated with risk scores as shown in (A). C: The overall survival rate of the cases with a T3 gastric cancer (n ϭ 73) was determined based on their risk scores.…”
Section: Discussionmentioning
confidence: 99%
“…Using the Surveillance, Epidemiology, and End Results database, Coburn et al [30] found that only 29% of 10,807 resected gastric cancer patients had Ն15 lymph nodes examined. In a study from the United Kingdom analyzing 18 hospitals, only 31% of the 699 surgical resections resulted in Ն15 lymph nodes analyzed [31]. Thus, many western patients are understaged following surgical resection of their gastric cancers because of inadequate lymph node sampling.…”
Section: Potential Benefits Of More Extensive Lymphadenectomiesmentioning
confidence: 99%